Gender and justice in multicultural liberal states - Deveaux, Monique; Oxford eBooks (Oxford : Oxford University Press, 2006)
This work offers a persuasive argument for reconciling the tensions that arise when liberal democratic states try to protect two important kinds of equality: sexual equality and cultural equality.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Women's rights; Minorities -- Civil rights; Cultural pluralism; Multiculturalism; Culture conflict; Toleration; Social justice; Sex role; Liberalism; Electronic books